2013
DOI: 10.1111/brv.12060
|View full text |Cite
|
Sign up to set email alerts
|

Maternal care and subsocial behaviour in spiders

Abstract: While most spiders are solitary and opportunistically cannibalistic, a variety of social organisations has evolved in a minority of spider species. One form of social organisation is subsociality, in which siblings remain together with their parent for some period of time but disperse prior to independent reproduction. We review the literature on subsocial and maternal behaviour in spiders to highlight areas in which subsocial spiders have informed our understanding of social evolution and to identify promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 187 publications
(484 reference statements)
0
96
0
7
Order By: Relevance
“…It is unclear whether empathy is a key factor in motivating such behaviors, given that, in most of these cases, parent intervention is not triggered by the needs of the offspring (which could reveal sensitivity to others’ internal states), but rather by external danger stimuli activating defensive behavioral responses (Rosenblatt, 2003). For example, in some species of spiders the young remain with the mother for an extended period, during which time the mothers provide food and defense (Yip and Rayor, in press). Mammals evolved more complex behavioral strategies to cope with immature offspring, possibly because such prolonged maternal care is necessary to facilitate offspring weaning and independence (Olazábal et al, 2013).…”
Section: Evolutionary Precursors Of Empathymentioning
confidence: 99%
“…It is unclear whether empathy is a key factor in motivating such behaviors, given that, in most of these cases, parent intervention is not triggered by the needs of the offspring (which could reveal sensitivity to others’ internal states), but rather by external danger stimuli activating defensive behavioral responses (Rosenblatt, 2003). For example, in some species of spiders the young remain with the mother for an extended period, during which time the mothers provide food and defense (Yip and Rayor, in press). Mammals evolved more complex behavioral strategies to cope with immature offspring, possibly because such prolonged maternal care is necessary to facilitate offspring weaning and independence (Olazábal et al, 2013).…”
Section: Evolutionary Precursors Of Empathymentioning
confidence: 99%
“…Ultimately, permanent sociality is achieved by the complete elimination of pre-mating dispersal. Maternal care is widespread amongst arachnids (Yip and Rayor 2014) and it seems likely that extended maternal care and the resulting formation of family sibling groups is a pre-condition for sociality to evolve . For the maintenance of group cohesion, juvenile dispersal has to be delayed to prolong the time of intraspecific interaction, mainly between mother and offspring, to allow selection to act on behaviours that facilitate further social evolution.…”
Section: Evolution Of Sociality In Arachnidsmentioning
confidence: 99%
“…This might well be an artefact of a biased investigation, but it may also underpin the importance of kin recognition to facilitate the evolution of sociality in these animals. In spiders, kin recognition mechanisms are subtle and comprise a number of specific behaviours that are often highly contextdependent (Yip and Rayor 2014). Those mechanisms may be used to direct help towards related individuals in social groups or to discriminate against foreigners.…”
Section: Kin Recognition In Subsocial Spidersmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsocial and social spiders communally hunt and feed on large prey items (Avilés 1997;Lubin and Bilde 2007;Yip and Rayor 2014), and it has been shown that competition is reduced when group members are closely related (Schneider and Bilde 2008;Ruch et al 2009). …”
Section: Introductionmentioning
confidence: 99%